Freedom, Union, and Power Lincoln and His Party in the Civil War - Green, Michael (The North's Civil War, 2022)
Freedom, Union, and Power analyzes the beliefs of the Republican Party during the Civil War, how those beliefs changed, and what those changes foreshadowed for the future. The party's pre-war ideology of "free soil, free labor, free men" changed with the Republican ascent to power in the White House. With Lincoln's election, Republicans faced something new-responsibility for the government. With responsibility came the need to wage a war for the survival of that government, the country, and the party. And with victory in the war came responsibility responsibility for saving the Union-by ending slavery-and for pursuing policies that fit into their belief in a strong, free Union. Michael Green shows how Republicans had to wield federal power to stop a rebellion against freedom and union. Crucial to their use of federal power was their hope of keeping that power-the intersection of policy and politics